The long road home / Lori Wick - Wick, Lori
Blinded by bitterness, Paul Cameron leaves his church and flees to a logging camp deep in the north woods of Wisconsin. There he wrestles with his loss-unable to get Corrine out of his mind and unbilling to make peace with God.